2000
DOI: 10.1262/jrd.46.341
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Immune System in Behavioral Strategies of Reproduction

Abstract: Abstract. Since both reproduction and immunocompetence are costly, the negative reciprocal relationships between these functions were found in many species. Due to reproductive immunosuppression, some fraction of seasonally breeding populations of small mammals reproduces in the first breeding season, while others reproduce in the next one. Elevation of breeding efforts under the increased risk of mortality and the reproductive delay until recovery are the polar variants of mating behavior of parasitized indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 205 publications
(200 reference statements)
1
6
0
1
Order By: Relevance
“…Self-maintenance costs, among others, include expenses for immunity. However, although activation of immune response is a demanding process, immune maintenance is thought to be cheap and a trade-off between immune homeostasis and reproductive effort is a matter of debate 12 15 . To address a role of immune maintenance in reproduction, we surveyed reproductive phenotypes in mice knockout for tumor necrosis factor (TNF-KO) free of specific pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Self-maintenance costs, among others, include expenses for immunity. However, although activation of immune response is a demanding process, immune maintenance is thought to be cheap and a trade-off between immune homeostasis and reproductive effort is a matter of debate 12 15 . To address a role of immune maintenance in reproduction, we surveyed reproductive phenotypes in mice knockout for tumor necrosis factor (TNF-KO) free of specific pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Since all of the studied pathogens have other tropism than the urogenital area, it is unlikely that their influence on male sexual signals is by means of their metabolites being released in host urine. A more credible explanation of the phenomenon seems to be that a secondary effect of an infection is infection‐induced immune and neuroendocrine responses to the parasitic antigens [11,12]. One effect of the antigenic challenges on the male scent attractiveness was demonstrated in several experiments using simulation of an acquired immune response by means of an injection with strange antigens such as sheep red blood cells and a thermophilic strain of Salmonella enterica .…”
Section: Introductionmentioning
confidence: 99%
“…heterozygote and rare allele advantage, inbreeding avoidance; reviewed by Eklund 1994 andPenn &Potts 1999). However, while sexual selection is traditionally considered to include inter-and intrasexual components (Moshkin et al 2000;Moore et al 2001;Olsson et al 2003), it has not been shown whether the MHC also contributes to male competitive behaviour.…”
Section: Introductionmentioning
confidence: 99%